Surgical treatments on adult tethered cord syndrome: A retrospective study. Issue 46 (November 2016) - Gao, Jun; Kong, Xiangyi; Li, Zhimin; Wang, Tianyu; Li, Yongning
Abstract : Abstract: To investigate effects of surgical treatment on adult tethered cord syndrome (TCS). A retrospective analysis of 82 adult patients (17 male cases, 82% and 24 female cases, 59%) with TCS treated by surgery was conducted between March, 2005 and December, 2015, with an average age of 31.6 years and average disease course of 6.7 years. All the 82 cases of patients received nerve electrophysiology monitoring assisted microsurgery. After surgery, all patients were followed up for an average of 2.5 years. Surgical effects were evaluated according to Hoffman grading system. As this is just a retrospective study that does not involve any interventions, ethical approval was not necessary according to the rules of the hospital. All patients were followed up, no death occurred. According to Hoffman grading system, the neurologic symptoms were improved in 22 patients (27%), stabilized in 60 patients (73%). Of 10 cases with lipoma tethered spinal cord, corresponding symptoms were improved in 2 cases. Of 32 cases with tethered spinal cord caused by dermoid cyst and epidermoid cyst, the symptoms were improved in 6 cases. Of 40 cases without occupying lesions of tethered spinal cord, the symptoms were improved in 14 cases. Besides, there was no deteriorated case. Surgical treatment on adult patients with TCS can improve the neurologic deficits which are associated with the course of disease, early treatment has much better curative effect.